One-week L-arginine supplementation had no effect on 200m freestyle swimming time trial in moderately-trained male swimmers - Esen, O.; Karayigit, R. (Journal of Dietary Supplements, 2023)
Research on the effect of L-arginine supplementation on exercise performance is still inconsistent and its influence on single-bout swimming performance has not been investigated. Therefore, the aim of this study was to assess if one-week L-arginine supplementation would enhance 200-m freestyle swimming performance in trained/developmental (regularly training ~3 times per week with a purpose to compete) male swimmers. In a randomized, cross-over, double-blind design, 8 trained/developmental male swimmers (age 25 ± 5 years; mean ± SD) completed 200-m freestyle swimming time-trial on 3 separate occasions: a control trial; and after 2 separate 7-d supplementation periods, with a daily dose of either 8 g/d of L-arginine or placebo trials. Blood lactate concentration was measured immediately post time-trial swimming. Completion time of the 200-m freestyle swimming time-trial did not differ significantly (F = 4.55; P = 0.060; Etap2 = 0.394) between control (149.40 ± 9.88 s), L-arginine (146.02 ± 10.34 s) and placebo trials (147.58 ± 10.86 s). There was no statistically significant difference in post time-trial swimming blood lactate concentration between trials (control: 11.2 ± 2.7; L-arginine: 13.1 ± 1.8; Placebo: 12.2 ± 2.7, F = 3.52; P = 0.058; Etap2 = 0.335). One-week of supplementation with 8 g/d of L-arginine, had no ergogenic effect on middle-distance (200-m), freestyle swimming performance in trained/developmental male swimmers.